TRAINING OF FUTURE OFFICERS OF THE ARMED FORCES OF UKRAINE FOR PROFESSIONAL ACTIVITY IN MILITARY LYCEUMS AS A PEDAGOGICAL PROBLEM - Bondarenko, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
In the scientific article the training of future officers for professional activity in military lyceums is considered as not only theoretical but also practical component, because without the theoretical component in combination with practice it is impossible to orient properly in the educational process of higher military educational institutions and military training units of higher educational institutions during the training of tactical level officers and the assessment of training final results. The training of future officer of the Armed Forces of Ukraine for professional activity in military lyceum is considered and scientifically substantiated both as a purpose and as a result of professional training. Since the main purpose of any higher military educational institution is to prepare the graduates for professional activity, the main guideline and basis for solving the problems of training of future officers for professional activity should undoubtedly be the essence of this activity, which reflects the set of its deep connections, relations and internal laws. The detailed analysis of the scientific works provided grounds to substantiate the author’s determination of training of future officers of the Armed Forces for professional activity in military lyceum, which provides the formation of a holistic personal education as a result of special professional and psychological-pedagogical professional training, which ensures the transition to a qualitatively new form of activity for the cadet as a future officer of the Armed Forces and it is a set of interdependent and interconnected components: motivational-value, cognitive and reflexive. The criterias of readiness for professional activity of an officer of the Armed Forces of Ukraine as an important and defining feature that characterizes various qualitative aspects, essences and specifics of professional activity of a serviceman are evaluated. The professional activity of an officer of the Armed Forces of Ukraine in a military lyceum is characterized by a high degree of social responsibility, conservatism of values and clear regulation of the conditions for its implementation. In the professional environment of the military lyceum, the role of socially conditioned characteristics and conditions of activity of both faculty that includes officers of the Armed Forces, and pupils (lyceum students) is significantly increasing. It follows that mastering the profession of an officer of the Armed Forces is not only the ability to effectively perform duties, but also the adoption of the appropriate lifestyle, way of thinking, system of norms and values by a future officer.